2023
DOI: 10.1111/edt.12829
|View full text |Cite
|
Sign up to set email alerts
|

The outcomes of auto‐transplanted premolars in the anterior maxilla following traumatic dental injuries

Abstract: Background/Aims: Tooth auto-transplantation is a treatment option, which is often not considered to replace anterior maxillary incisors in children and adolescents.There are multiple prognostic factors that may influence the outcomes of premolar auto-transplantation, but there is limited evidence from human studies. The aim of this study was to report the outcomes of auto-transplanted premolars in the anterior maxilla following traumatic dental injuries (TDIs) and to identify their prognostic factors. Material… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 48 publications
0
21
0
Order By: Relevance
“…desirable rootto-crown ratio), yet still has an open apex at the time of autotransplantation is an ideal donor candidate, as there is still enough room at the apex for revascularization. 2 It has been suggested that the ideal age for transplanting premolars is approximately 12 years of age, 25 as the completion of root development of these teeth has been reported to occur around 13-14 years of age. 49 Despite this suggestion, this case series demonstrates favourable autotransplantation outcomes in patients ranging in age from 9 years and 5 months to 13 years old at the time of the surgical procedure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…desirable rootto-crown ratio), yet still has an open apex at the time of autotransplantation is an ideal donor candidate, as there is still enough room at the apex for revascularization. 2 It has been suggested that the ideal age for transplanting premolars is approximately 12 years of age, 25 as the completion of root development of these teeth has been reported to occur around 13-14 years of age. 49 Despite this suggestion, this case series demonstrates favourable autotransplantation outcomes in patients ranging in age from 9 years and 5 months to 13 years old at the time of the surgical procedure.…”
Section: Discussionmentioning
confidence: 99%
“…24 A recent study has reported the survival and success rates to be 93% and 80% respectively, for transplanted premolars into the anterior maxilla following dental trauma. 25 Survival has been defined as the transplanted tooth still being present in situ, with or without meeting specific success criteria, 26 with no presenting indication for extraction. 27 Although there is no current consensus regarding the definition of success for a transplanted tooth, 28 it has been suggested that a successful transplant should satisfy the following criteria: normal clinical and radiographic findings; no evidence of ankylosis; no progressive resorption or infection; a crown-to-root ratio close to normal; normal mobility and gingival contour; and normal gingival pocket depth.…”
Section: Introductionmentioning
confidence: 99%
“…The item identification process was used to generate a preliminary list of items from different sources: Systematic literature review to identify studies examining the outcome from autotransplantation of developing teeth in humans were included. The systematic review methods are described in full in Table S1. Guidelines published by the International Association for Dental Traumatology, International Association of Paediatric Dentistry, British Society of Paediatric Dentistry and American Association of Endodontics were searched to identify any recommendations or guidance relating to tooth autotransplantation or management of tooth avulsion. Review of transcripts from interviews with people with experience of tooth autotransplantation, including young people, parents and dental professionals, which were undertaken in the Leeds Dental Institute for another study 18 …”
Section: Methodsmentioning
confidence: 99%
“…3. Review of transcripts from interviews with people with experience of tooth autotransplantation, including young people, parents and dental professionals, which were undertaken in the Leeds Dental Institute for another study. 18 Patient and procedural characteristics and outcomes were extracted and synthesised into categories:…”
Section: Stage One: Item Identificationmentioning
confidence: 99%
“…Not only does this special issue offer an up-to-date review and synthesis of the evidence supporting the use of tooth autotransplantation, 4,5 it also offers a consensus-led autotransplantation core outcome set, 6 and an index for reporting the success of this technique which will help streamline future research in this field. 5 In addition, this special issue presents the results of original research assessing the long-term outcomes of 144 anterior and 1654 posterior transplanted teeth, 7,8 and the use of new technologies to improve the outcome of autotransplantation. 9 Furthermore, this special issue offers a step-bystep guide for autotransplantation which is provided to support clinicians embarking on this technique.…”
Section: E D I T O R I a Lmentioning
confidence: 99%